(untitled) (Nigerian Journal of Technology, 2017)
The anti-corrosion properties of paints can be optimised when adequate proportion of the paint constituents are used. Effect of zinc powder addition to Villa Gloss and Silka Lux Marine Enamel paints on corrosion resistance of mild steel was studied. Quantitative Analysis and Potentiodynamic Polarisation Technique were used to evaluate the samples. The results indicate that zinc powder addition between 15 and 25 % significantly reduced the corrosion rate. The corrosion rate stabilized at approximately 0.10 mmpy when zinc powder added was above 15 %, independent of the exposure time. Potentiodynamic anodic polarization curves of the samples immersed in seawater showed that sample with 25% zinc powder addition exhibited highest corrosion potential and the least corrosion current density. Microstructural analysis of the samples also revealed the presence of pitting corrosion at the surfaces of the samples and their geometry, volume fraction and distribution vary with the zinc powder addition. http://dx.doi.org/10.4314/njt.v37i1.21